Do Foreign Direct Investment (FDI) Inflows Stimulate Export Performance in Bangladesh? - Islam, Mohammad Mohidul (Current Topics on Business, Economics and Finance Vol. 4, 2023)
Considering FDI inflows as an important factor to enhance the export performance in developing economies, this study attempts to investigate the relationship between FDI inflows and export performance in Bangladesh using historical data from 1995 to 2020. The empirical analysis is conducted by applying Johansen cointegration approach and Vector Error Correction Mechanism (VECM) in examining the long run relationship as well as the short run dynamics between FDI inflows and export receipts. According to the study's findings, the export receipts have statistically significant positive relationship with FDI inflows in the long run. As the error correction mechanism indicates that the dynamic convergence towards long run equilibrium has not been found in a consistent way, hence the short-term dynamic adjustments are not statistically established. However, this study suggests that the government should take proper initiatives through infrastructure development in exporting industries to attract higher FDI inflows for accelerating improving export performance.